Utilizing Merdeka Mengajar Platform at SMP Muhammadiyah Bandung - Rima Suryadi; Dian Hidayati (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
Based on observations in the school in the school year 2022-2023, not all teachers are familiar with the implementation of the independent curriculum and the use of the Merdeka Mengajar platform, but they have to directly implement learning using the independent teaching platform, so the school conducts internal coaching and training for these teachers by inviting supervisory resource persons from the Bandung City Education Office. This research uses a qualitative descriptive method by collecting data through observation, literature review and focus group discussion (FGD). The focus of the research is the use of Merdeka Mengajar Platform by teachers at SMP Muhammadiyah 5 Bandung. With the use of Merdeka Mengajar Platform, it is hoped that the quality of learning at SMP Muhammadiyah 5 Bandung will improve in the coming years.